2019
DOI: 10.3390/agriculture9060119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rht-B1b and Ddw1 Dwarfing Genes in Two Connecting Populations of Spring Triticale under Greenhouse Experiment Conditions

Abstract: Dwarfing genes not only reduce the height of triticale plants, but also have pleiotropic effects on important agronomic traits. An important task for breeding is to evaluate the effects of gibberellin responsive (GAR) and gibberellin-insensitive (GAI) dwarfing genes in one genotype. In the greenhouse experiment, we evaluated the effects of the GAI gene Rht-B1b of wheat and the GAR gene Ddw1 of rye on height and the main agronomic traits in two connecting populations derived from crossing Ddw1 donors (cv. ‘Mudr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Braun et al [ 33 ] recently identified a gibberellin 2-oxidase gene ( ScGA2ox12 ) as a candidate for Ddw1 in rye, which is located at 862 Mbp on chromosome 5R. As Ddw1 has been reported in spring and winter triticale [ 14 , 17 , 31 , 35 ] and as the QTL region coincides with the position of Ddw1 , we conclude that the 5R QTL corresponds to Ddw1 . Ddw1 is present in 20 of the 129 registered cultivars analyzed in this study and appears to have been increasingly used in recent years.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Braun et al [ 33 ] recently identified a gibberellin 2-oxidase gene ( ScGA2ox12 ) as a candidate for Ddw1 in rye, which is located at 862 Mbp on chromosome 5R. As Ddw1 has been reported in spring and winter triticale [ 14 , 17 , 31 , 35 ] and as the QTL region coincides with the position of Ddw1 , we conclude that the 5R QTL corresponds to Ddw1 . Ddw1 is present in 20 of the 129 registered cultivars analyzed in this study and appears to have been increasingly used in recent years.…”
Section: Discussionsupporting
confidence: 61%
“…In wheat and rye, the founding species of triticale, a large number of height-reducing loci are known [ 21 , 27 , 28 , 29 , 30 ]. Of the major QTL located on the A or B genome that are used in wheat breeding and are therefore potentially suitable to be used in triticale breeding, Rht-B1 located on chromosome 4B has previously been reported in spring triticale [ 31 ]. QTL mapping in bi-parental triticale families has revealed several QTL on different chromosomes, but most of them with only small effects [ 14 , 17 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neverthelss, some authors observe some effect of Rht-B1 region on earliness that might be associated with putative genes located in the vicinity of Rht-B1 [ 52 , 62 ]. Later flowering / heading is observed in plants with GA-sensitive dwarfing genes [ 50 , 51 , 63 ]. Ppd-D1 had a much greater effect in Krasnodar, where Ppd-D1a accelerated heading by 5–7 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, beside reducing plant height, the dwarfing alleles Ddw1 may also reduce the grain weight per spike and the weight of 1000 grains. This negative effect of Ddw1 can be compensated for by the presence of Rht-B1b [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture 2020,10, x FOR PEER REVIEW 5 of 12 Figure 1. Capillary electrophoresis profiles of PCR amplification products for REMS1218 marker.…”
mentioning
confidence: 99%